STRATEGI KEPEMIMPINAN PENGASUH RUMAH QUR’AN DALAM MENINGKATKAN KINERJA GURU MELALUI METODE UMMI DI RAUDHATUL QUR’AN AL-ZAHRA KABUPATEN MURUNG RAYA - Safari, Akhmad; Hardian, Dafyar Eliadi; Darmojo, Hardjito S. (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
The smooth implementation of educational tasks depends heavily on the principal's ability to serve as principal. As an educational leader, the principal must assume full responsibility for the smooth implementation of teaching and learning activities at his/her school. Therefore, the principal plays a crucial role and carries significant responsibilities, requiring a high level of expertise in various fields, particularly in his/her role as a leader and manager in the implementation of the learning process at school. Leadership issues always leave a compelling impression, as the success or failure of an organization depends, among other things, on the quality of his/her role: the ability to influence, motivate, and direct the behavior of individuals or groups to achieve specific goals in specific situations. The principal, as the highest leader of the school, is considered successful if he/she is able to improve teacher performance through various learning activities that focus on teachers' abilities to practice teaching in the school. Therefore, the principal must be able to fulfill his/her roles and responsibilities as an education provider, educational leader, educational supervisor, and educational administrator, guiding other educational staff and utilizing and maintaining facilities and infrastructure. In addition to the principal's participatory leadership style influencing teacher performance, teacher motivation is also a factor. This study aims to analyze the influence of principal leadership and teacher work motivation on learning effectiveness, with teacher competency as an intervening variable. This study used a quantitative approach with a survey method because the data obtained from the research instrument are numerical and the data processing uses statistics. The results showed that principal leadership and teacher work motivation significantly influence learning effectiveness, with teacher competency as an intervening variable. Keywords: Principal Leadership, Teacher Work Motivation, Teacher Competency.